Determinants of Financial Well-Being in Strengthening Urban Local Economic Resilience (Evidence from SMEs in Kedungkandang District, Malang City, Indonesia) - Sodik; Sasangka, Jannatu Nugrahani Surya; Diningrat, Shafiyah Arya Chandra; Solikah (PANGRIPTA, 2026)
This study examines the determinants of financial well-being and their implications for strengthening urban local economic resilience, focusing on small and medium enterprises (SMEs) in Kedungkandang District, Malang. Within the framework of local economic development, financial well-being is conceptualized not only as an individual-level outcome but also as a strategic indicator of business sustainability and regional economic resilience. This research adopts a quantitative explanatory design, with data collected through structured questionnaires distributed to culinary SME owners. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both direct and mediated relationships among variables. The results indicate that intellectual capital and financial literacy have positive and significant effects on financial well-being. Both variables also demonstrate a significant negative effect on financial distress, which, in turn, negatively influences financial well-being. Furthermore, financial distress is found to partially mediate the relationship between intellectual capital, financial literacy, and financial well-being. From a regional development perspective, the findings suggest that strengthening knowledge-based capabilities and financial literacy among SMEs can reduce financial vulnerability and enhance business resilience. More importantly, these improvements contribute to the broader objective of strengthening local economic resilience in urban areas. This study offers practical implications for local governments and development stakeholders in designing SME-oriented policies, particularly those aimed at improving financial capacity, mitigating financial distress, and promoting sustainable urban economic resilience.